The justification of evaluation criteria of destruction material by embroidery needles - Ріпка, Галина Анатоліївна; Мазнєв, Євген Олександрович; Мичко, Анатолій Андрійович (Technology audit and production reserves, 2015)
Compound fabric pieces with a sewing machine leads to destruction of material. Extent of destruction of the sample depends on the number of needles and stitch step. It leads to change of explosive loading and coefficient of air permeability. But remains the question of influence of extent of destruction of material in the course of machine embroidery is not studied. The results of the researches, related to justification criteria for assessing material destruction by embroidery needles are in this work. needles number 75, 80, 90 and 100, and physical material model - polysiloxane (silicone) membrane, which is 0.1 mm of thickness,(50 × 200) mm of size and 83.0 N of breaking characteristic, were used for this experiment. Similar studies were carried out with the increasing of T seam imitation through the length and breadth of samplings, which are shown in the scheme. Such criteria as the change of values of tensile properties and the air permeability coefficient were used to evaluate the degree of destruction of samples, depending on their number and pitch of the seams. The experimental results, which are given in the article for the needle number 75. The experimental data indicate that as the change of the stitches pitch such process as machine embroidery, have been used, is interconnected multi function, and the embroidery needle is a destructive factor.